Sriwijaya Radio dan Kearifan Lokal melalui Bahasa Daerah Sumatera Selatan - Muhamad Firdaus; Badarudin Azarkasyi (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This investigation seeks to scrutinize the part played by Sriwijaya Radio in safeguarding indigenous knowledge by utilizing regional languages specific to South Sumatra. With the looming possibility of local languages dying out because Indonesian and foreign languages are so widespread, along with increased urbanization, and shifts in contemporary ways of living, Sriwijaya Radio has become a leading community media outlet that has always used the Palembang language in the programs it broadcasts ever since it was founded on July 13, 2002. A descriptive qualitative method is used in this study, and information is gathered through detailed conversations, observations, and records involving radio managers, broadcasters, program managers, and devoted Sriwijaya Radio listeners at its location on Jalan Seduduk Putih 1, Number 41A, 8 Ilir, Palembang, all of which took place on November 19, 2025. The study's conclusions show that Sriwijaya Radio is very important as a community media platform for protecting regional languages, and it does this through a number of tactics: (1) the consistent use of Palembang language, which includes the unique greeting